Wi-Fi Control of Mobile Robot Motion Types Based on Differential Drive Kinematics Modelling Approach - Ercan TASKIRAN; Yilmaz DURNA; Hasan KOCER (International Journal of Applied Methods in Electronics and Computers, 2016)
Recently, utilization of mobile robots has increased substantially. Accordingly, wireless communication is preferred in mobile robots. QBot 2 is an autonomous ground robot which is a new product of Quarc. The QBot 2 utilizes an onboard data acquisition card and a wireless embedded computer to measure the onboard sensors and drive motors. In this study, QBot 2 mobile robot is evaluated in terms of its ability to maneuver. In this way, controlling QBot 2 mobile robot in real time is planned while a command recognition system is developed. Connection with the QBot 2 is carried out in a wireless environment. A Simulink model is developed in MATLAB® environment. The created model is built with Quarc control software. Compiled model is downloaded with TCP/IP connection to QBot 2 and the application is carried out on an embedded computer. The QBot 2 mobile platform consists of two central drive wheels mounted on a common axis. This drive configuration is known as differential drive. The two drive wheels are independently driven forward and backward in order to actuate the robot. Motion of the wheels is realized using high performance DC motors. When the results are analyzed, 13 different motion types are observed in total. The observed motion types could be used as references in future works since many practical applications, such as the remote control of QBot 2 mobile robot via the human voice, require the availability of different motion types.